Methodological trends and perspectives of animal dietary studies by noninvasive fecal DNA metabarcoding. Issue 4 (17th August 2020) - Ando, Haruko; Mukai, Haruka; Komura, Taketo; Dewi, Tungga; Ando, Masaki; Isagi, Yuji
Abstract: Fine‐scale estimation of trophic interactions is an important subject in the field of ecology. Diet analysis based on fecal DNA metabarcoding has been accepted as a noninvasive, accurate, and time‐ and cost‐effective tool to determine animal diets. Here, we summarize the trends of fecal metabarcoding studies as well as methodological characteristics using 155 original papers published from 2009 to March 2020. We calculated the frequencies of the methods and conditions used in each experimental procedure and bioinformatics approach. Mammals were the major target taxa for fecal metabarcoding. A few methods or conditions dominated each procedure: sampling, DNA extraction, PCR, sequencing, and bioinformatics, which might be specialized for metabarcoding of degraded fecal DNA. However, the disadvantages of common methods were noted in some studies, and further optimizations are required to obtain more accurate dietary data with high taxonomic resolution and quantitative performance. This review will help fecal metabarcode users, especially new scientists who are considering using fecal metabarcoding in their studies, understand the process and common methods of fecal metabarcoding. We also hope this review will facilitate further technical improvements in this method. Abstract : We summarize the trends of fecal metabarcoding studies as well as methodological characteristics. Mammals were the major target taxa. A few methods or conditions dominated each procedure, which might be specialized for metabarcoding of degraded fecal DNA. However, further optimizations are required to obtain more accurate dietary data with high taxonomic resolution and quantitative performance.